The audit quality and the audit firm’ caracteristicts in Portugal - Prazeres, Carlos; Pais, C. (CISTI'2017, 2017)
This study relate the audit firms characteristics and the audit quality. Using data from the Portuguese listed companies from the period 2010 to 2014 and using as a proxy of audit quality the type of audit report, the conclusion is that the dimension of the audit firm and the audit fees on the total audit firm’s fee influences the audit quality. This study contributes to the literature by studying a country of a weak investor protection and after the financial 2008 crises, besides for the audit firm’ characteristics studied.